Iso‐electric focusing and the identification of fisheries’ waste in the diet of Westland petrels ( Procellaria westlandica ) - Amanda N. D. Freeman; Peter J. Smith (New Zealand Journal of Marine and Freshwater Research, 1998)
Iso‐electric focusing was used to identify fish tissue in Westland petrel ( Procellaria westlandica ) diet samples. Forty‐five percent of the samples from Westland petrel stomachs produced clear protein banding patterns and more than half of these were identified as species common in fisheries’ waste. Proteins in the other samples were presumably too digested for this technique. Iso‐electric focusing is a comparatively quick and inexpensive technique and is particularly useful for diet studies where flesh eaten is likely to be relatively undigested at the time of sampling.